Payload Oscillations Minimization via Open Loop Control. - Kosucki, Andrzej (Lodz University of Technology. Faculty of Mechanical Engineering. Department Division of Dynamics., 2017)
The results of tests of payload oscillations, forced by linear control function which allows to minimize payload sway after acceleration phase and after overhead crane stopping are presented in this paper. The analysis of solution of this problem has been carried out. The algorithm of operation for real drive system which takes into account the possibilities of driving of an overhead crane is also presented. The impact of inaccuracies of measurement of the ropes length on minimizing a displacements of payload during the duty cycle is shown as well. The correctness of the method is confirmed by results both simulation and experimental tests.
Keywords: payload oscillations; oscillations minimization; underactuated; systems; crane drives; oscylacje ładunków; minimalizacja oscylacji; niedokładne systemy; napędy żurawia